Securing The Future Of Smart Farming: How Blockchain And IPFS Can Protect Sensor Data For Sustainable Precision Agriculture (Journal of Namibian Studies : History Politics Culture, 2023)
Blockchain technology has shown promise for applications beyond cryptocurrencies by enabling new forms of decentralized data management and value exchange. One sector that could benefit is agriculture through innovations in precision monitoring and resource allocation. Traditionally, smart farming systems rely on centralized platforms to integrate sensor data from fields and facilities. However, this model presents challenges around data security, access control and single points of failure. By developing a prototype combining blockchain and Internet of Things (IoT) technologies, we aimed to address these limitations and validate an alternative approach. Our solution integrated moisture sensors with a wireless network module to securely transmit real-time measurements to a distributed ledger. This allowed recorded data to be accessed remotely via a mobile application. By demonstrating this decentralized protocol for collecting, recording and viewing sensor data, our work indicates the potential of blended blockchain and IoT technologies to enable transparent and long-term sharing of agricultural insights. Moving away from centralized systems through this proof-of-concept paves the way for more resilient and sustainable models of precision agriculture informed by distributed sensor records over time. In summary, our prototype provided a working example of how integrating blockchain into an IoT network can validate new governance frameworks for agricultural data storage and access beyond traditional cloud-dependent models. This offers opportunities to further optimize farming resources and operations through transparent sensor-driven decision making.